Physicochemical Changes, Bioactive Compound Dynamics, and Proteomic Remodeling During Ligustrum sp. Fruit Development - Gilson Gustavo Lucinda Machado; Elda Eller; Ana Beatriz Silva Araújo; Camila Giovana Carvalho Souza; Cháid Acácio António Mussalafo; Carlos Alexandre Rocha da Costa; Sidney Vasconcelos do Nascimento; Sayure Mariana Raad Nahon; Alice de Paula de Sousa Cavalcante; Isa Rebecca Chagas da Costa; Rafael Borges da Silva Valadares; Elisângela Elena Nunes Carvalho; et al. (Plant Molecular Biology Reporter, 2026)

When Herbicides Interact: Synergistic, Additive, and Antagonistic Effects of 2,4-D- and Glyphosate-Based Herbicides in Physalaemus cuvieri Tadpoles - Vrandrieli Jucieli Skovronski; Aline Pompermaier; Camila Fátima Rutkoski; Natani Macagnan; Alexandre Folador; Gilcinéia dos Santos; Márcio Borges-Martins; Paulo Afonso Hartmann; Marilia Hartmann (Water, Air, & Soil Pollution, 2026)
Considering the ecological relevance of amphibians and the widespread agricultural use of herbicide mixtures, investigations addressing their joint toxicological effects are increasingly necessary. Here, we investigated the effects of a mixture of two commercially formulated herbicides widely used in combination in agriculture—2,4-D-based herbicide (DBH) and a glyphosate-based herbicide (GBH)—on tadpoles of Physalaemus cuvieri , a bioindicator amphibian species. Chronic tests were performed using environmentally relevant concentrations and the maximum concentrations permitted in water bodies by current legislation. The mixture of these two pesticides impaired tadpole survival and induced abnormal behavior, characterized by distinct responses patterns. Nearly half of the analyzed tadpoles exhibited malformation by the end of assay. The integrated analysis of survival, behavior, and malformation data revealed antagonistic, additive and synergistic interactions between DBH and GBH in Physalaemus cuvieri tadpoles. These findings demonstrate that the herbicide mixture is nonetheless lethal to the tested species, inducing changes that can compromise its survival and overall living conditions, which may lead to significant biological impacts.

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Productive, metabolic and economic responses of Nellore young bulls fed diets with different non-protein nitrogen source combinations - Luiz Antonio Rodrigues; Priscilla Dutra Teixeira Borges; Camila Celeste Brandão Ferreira Ítavo; Gelson dos Santos Difante; Alexandre Menezes Dias; Vanessa Zirondi Longhini; Manoel Gustavo Paranhos da Silva; Lívia do Nascimento Gomes; Adrianni Dias Borges; Hevelyn de Almeida Cunha; Luís Carlos Vinhas Ítavo (Tropical Animal Health and Production, 2026)
Nutrition is a key determinant of performance, carcass traits, and production efficiency in beef cattle. In this context, feed additives have emerged as a promising strategy to enhance nutrient utilization and reduce production costs. We aimed to evaluate the effects of replacing urea with a product extruded urea enriched with essential oils (NFeed ® ) on nutrient intake, performance, blood parameters, and feed cost in feedlot-finished Nellore young bulls. Twenty-four non-castrated animals with an average initial body weight of 394.6 ± 53 kg were randomly assigned in a completely randomized design, following the treatments considering different combinations of NPN source in diet: 0% NFeed (100% of non-protein nitrogen from urea), 50% NFeed (50% of non-protein nitrogen from urea and 50% of non-protein nitrogen from NFeed), 75% NFeed (25% of non-protein nitrogen from urea and 75% of non-protein nitrogen from NFeed) and 100% NFeed (100% of non-protein nitrogen from NFeed). Final body weight, total weight gain, and average daily gain had a linear response, with the highest values in the 100% NFeed treatment. Feed efficiency and feed conversion exhibited linear effects, with the 100% NFeed diet resulting in the greatest feed efficiency and the lowest feed conversion. A quadratic effect was observed for plasma urea, and gamma-glutamyl transferase levels. The replacement of conventional urea with extruded urea enriched with essential oils (NFeed) represents a viable nutritional strategy for finishing beef cattle in feedlot systems. Increasing levels of NFeed linearly improved animal performance while maintaining similar feed intake, increasing feed efficiency reducing feed conversion, and the cost per kilogram of body weight gain. Thus, we recommend a partial replacement of urea by NFeed as a non-protein source in beef cattle feedlot.

Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

Rotavirus Outbreak Traced in Clinical, Environmental, and Food Matrices: Whole Genomic Characterization of an Equine-like G3P[8] Genotype - Fernanda Marcicano Burlandy; Bruna Campestrini Casarin; Meylin Bautista Gutierrez; Carina Pacheco Cantelli; Shênia Patricia Corrêa Novo; Rosane Maria Santos de Assis; Bruna Candia Piccoli; Amanda Haisi; Anelise da Costa Daneli; Roberta Danieli Marchesan; Julia Kuhns; João Pessoa Araújo Junior; et al. (Food and Environmental Virology, 2026)
The emergence of new viral strains has been frequently associated with the onset of outbreaks in different epidemiological settings. This study investigated an acute gastroenteritis (AGE) outbreak, which occurred at a university campus in southern Brazil, in 2024, affecting approximately 30–40% of undergraduate students, with over 400 reported cases. The objectives were to describe the epidemiological and molecular features of the outbreak, identify the probable transmission route, and assess the genetic relatedness of the detected strain to recently circulating rotavirus A (RVA) lineages. Clinical, environmental, and food samples were analysed for RVA and norovirus genogroup (G) I and GII. RT-qPCR detected RVA in the three specimen types with concentrations reaching 2.4 × 10 8 genome copies (GC)/g in faeces, 3.5 × 10 2 GC/g in food and 5.5 log₁₀ GC/l in water. Genotyping revealed an equine-like G3P[8] strain in clinical samples with whole genome sequencing establishing a DS-1-like backbone; G3-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2. Sequencing data of the VP6 gene of RVA detected in one of the environmental samples confirmed the same genotype (I2), consistent with the genotype found in the clinical stool samples. The detection of RVA in multiple environmental and food specimens suggests that the possible source of contamination was associated with water supply systems. Phylogenetic analyses showed that the outbreak strain clustered with equine-like G3P[8] lineages. These findings highlight the importance of integrating molecular surveillance and environmental monitoring to trace viral transmission pathways and detect the emergence of RVA strains in community outbreaks.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Evaluation of models for estimating land-based plastics entering the ocean in countries of the Global South - Alexandre Rodrigues Mariano; Maria Eduarda da Silva Brocca; Bruna Cerati Carvalho; Ailton Borges Rodrigues; Sebastião Roberto Soares (Journal of Hazardous Materials, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Dynamic Transitions in Fish Community Composition From the Amazon River Plume to Offshore Reefs - Osmar J. Luiz; Bruno E. Soares; Lucas T. Nunes; Israel Hidenburgo Cintra; Ronaldo Borges Barthem; Alexandre P. Marceniuk (Journal of Biogeography, 2026)
Aim To investigate the spatial and temporal dynamics of fish assemblages across the Northern Brazilian Shelf, a vast and complex ecosystem influenced by the Amazon River plume, we aimed to identify fish assemblage types, understand transitions between them from the river mouth to offshore reefs, and examine seasonal changes related to plume dynamics. Location Northern Brazilian Shelf (Western Atlantic Ocean), from the Amazon River mouth to the Great Amazon Reef System (GARS). Taxon Actinopterygii and Elasmobranchii. Methods We applied a presence‐absence Latent Dirichlet Allocation (LDA) model to fish occurrence records. This Bayesian mixed‐membership probabilistic approach inferred latent assemblages by analysing co‐occurring species and quantifying community types at the same site in varying proportions, suitable for characterising transitions. We then mapped these assemblages' proportional contributions and analysed their spatial distribution relative to seasonal changes in river discharge and freshwater plume influence. Results Four fish assemblages were identified with a clear coast‐to‐offshore zonation: (1) freshwater‐tolerant plume assemblage near the river mouth; (2) an estuarine–mud–plain assemblage on the inner shelf; (3) a mixed‐sand corridor assemblage in mid‐shelf; and (4) a reef‐associated assemblage on outer‐shelf GARS. The first three assemblages showed a seasonal reorganisation. During the wet season, strong plume influence led to spatially segregated assemblages. Conversely, the dry season's reduced plume resulted in increased community overlap, centred on the mid‐shelf assemblage. The reef assemblage (4) remained spatially stable across seasons. Main Conclusions The Amazon River plume's seasonal dynamics primarily drive fish community structure and connectivity across the Northern Brazilian Shelf. This study uncovers how assemblages transition from being shaped by environmental filtering (exhibiting strong zonation during peak plume) to a more overlapping distribution as plume influence weakens. These findings underscore the need for dynamic, seasonally adjusted management to conserve biodiversity and ecosystem function in this significant, and increasingly threatened, estuarine–marine transition zone.

1-Butanol applied to ‘Maxi Gala’ apples during postharvest shelf life and after dynamic controlled atmosphere: Effects on metabolism and quality - Barbara Cecconi Deon; Fernanda de Candido de Oliveira; Francis Júnior Soldateli; Carine Borges Batista; Manoela Meira Balzan; Aline de Cássia Machado; Auri Brackmann; Vanderlei Both; Daniel Alexandre Neuwald; Fabio Rodrigo Thewes; Roger Wagner (Postharvest Biology and Technology, 2025)

Ecological risks of imidacloprid and tebuconazole in tropical freshwater invertebrates: Single and mixture implications - David Silva Alexandre; Vanessa Borges da Costa; Diego Ferreira Gomes; Mariana Amaral Dias; Cassiana Carolina Montagner; Evaldo Luiz Gaeta Espíndola; Thandy Junio da Silva Pinto (Aquatic Toxicology, 2025)

Gut microbiota and NLRP3 inflammasome activation in hemodialysis patients: exploring the link with systemic inflammation - Denise Mafra; Livia Alvarenga; Ludmila F.M.F. Cardozo; Júnia Schultz; Alexandre Soares Rosado; Natália A. Borges (Molecular Biology Reports, 2025)

Hippocampal Interneurons Shape Spatial Coding Alterations in Neurological Disorders - Juliane Midori Ikebara; Renata Silva Jorge; Luciana Simões Rafagnin Marinho; Guilherme Shigueto Vilar Higa; Avishek Adhikari; Fernando M. C. V. Reis; Fernando S. Borges; Henning Ulrich; Silvia Honda Takada; Roberto De Pasquale; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2025)

Developmental and behavioral traits of tropical amphipod Hyalella meinerti can be impaired by polyethylene microplastics - David Silva Alexandre; Gleyson Borges Castro; Isabele Baima Ferreira Freitas; Thandy Junio da Silva Pinto; Mariana Amaral Dias; Cassiana Carolina Montagner; Evaldo Luiz Gaeta Espíndola (Ecotoxicology, 2025)

Carbon-related processes as indicators of soil health in a degraded dryland area under long-term restoration: Responses of a 21-year grazing exclusion system - Antonio Y.V. Lima; Maurício R. Cherubin; Danilo F. Silva; Ademir S.F. Araujo; Diogo P. Costa; Jaedson C.A. Mota; Ícaro V. Nascimento; Alexandre S. Queiroz; Erika V. Medeiros; Kaio G.V. Garcia; Gabriel N. Nóbrega; Geocleber G. Sousa; et al. (Applied Soil Ecology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Metabolomics and proteomics of Campomanesia pubescens fruits throughout developmental stages - Gilson Gustavo Lucinda Machado; Carlos Alexandre Rocha da Costa; Elda Veiga; Sidney Vasconcelos do Nascimento; Sayure Mariana Raad Nahon; Alice de Paula de Sousa Cavalcante; Isa Rebecca Chagas da Costa; Rafael Borges da Silva Valadares; Elisângela Elena Nunes Carvalho; Kalynka Gabriella do Livramento; Eduardo Valério de Barros Vilas Boas (Food Chemistry, 2025)

Contamination status and evaluation of metal pollution indexes in sediments from shrimp farming in the Lower São Francisco River region, Northeast Brazil - Larissa Santos Xavier; Joel Marques da Silva; Andrielle dos Santos de Jesus; João Batista Pereira; Amanda Silva de Jesus; Marcos Vinicius Teles Gomes; Sarah Adriana Rocha Soares; Andrea Novelli; Elisângela Andrade Passos; Rennan Geovanny Oliveira Araujo; Carlos Alexandre Borges Garcia; Felipo Obed Correia; et al. (Journal of Soils and Sediments, 2025)

Static and dynamic controlled atmosphere storage and 1-methylcyclopropene treatment of ‘Cripps Pink’ apples: Linking sensory perception, volatile compounds, and quality - Fernanda de Candido de Oliveira; Manoela Meira Balzan; Barbara Cecconi Deon; Madison Willy Cordeiro; Carine Borges Batista; Francis Júnior Soldateli; Lucas Mallmann Wendt; Fabio Rodrigo Thewes; Vanderlei Both; Auri Brackmann; Daniel Alexandre Neuwald; Roger Wagner (Food Research International, 2025)

Impact of carbon footprint of food production on consumer perceptions and attitudes: Insights from text highlighting - Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Alexandre Henrique Silas Souza; Fabiana Borges Ribeiro; Taynara de Oliveira Ferreira; Laura Falavinha Vieira Bresciani; Jéssica Ferreira Rodrigues (Food Quality and Preference, 2025)

Trace metal chemical fractionation in airborne particulate matter from a tropical urban area in Brazil - Silvânio Silvério Lopes Costa; Jeferson Cavalcante Alves; Erivaldo Vieira da Silva; Joel Marques da Silva; Larissa Santos Xavier; Vaniele Souza Ribeiro; Dayara Virgínia Lino Ávila; Sidnei Oliveira Souza; Carlos Alexandre Borges Garcia; Gisele Olímpio da Rocha; Rennan Geovanny Oliveira Araujo (Environmental Science and Pollution Research, 2025)

Potential of Lacewings (Neuroptera: Chrysopidae) as Predators of the Red Gum Lerp Psyllid Glycaspis brimblecombei (Hemiptera: Aphalaridae) in Eucalyptus - Delane Patez Porto; Rosangela Cristina Marucci; Alexandre dos Santos; Nívia Borges Palhari; Caroline Silva Abreu; Brígida de Souza (Neotropical Entomology, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

Using native soil to cultivate seedlings of the threatened Melanoxylon brauna Schott (Fabaceae): A path for ex-situ conservation - Nayara Mesquita Mota; Bárbara Emanuelly Santos Souza Sales; Juliano Cezar Zonzini Borin; Eduardo Euclydes de Lima e Borges; Evandro Alexandre Fortini (Journal for Nature Conservation, 2025)

Clinical and epidemiological aspects in equine aural plaques - Gabryele Gomidy Rodrigues; Dara Santos Alves; Cristiana Raach Bromberger; Quintiliano Siqueira Schroden Nomelini; Alexandre Secorun Borges; José Paes de Oliveira-Filho; Diego José Zanzarini Delfiol (Veterinary Research Communications, 2025)

Evaluation of metals in surface sediments from shrimp farming areas in the estuarine region of the Baixo São Francisco, in Northeastern Brazil - Larissa Santos Xavier; Raynne Aparecida de Sousa Pires; Marcos Vinicius Teles Gomes; Elisângela Andrade Passos; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Felipo Obed Correia; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Evaluation of shrimp farming impacts on the water quality of the Lower São Francisco watershed region, Brazil - Rômulo André Santos Silva; Gustavo Andrade Araujo Oliveira; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Marcos Vinicius Teles Gomes; Adnívia Santos Costa Monteiro; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Bovine bone–based activated carbon composite containing nanomagnetite as a catalyst for photo-Fenton reactions - Thays de Oliveira Guidolin; Mariana Borges Polla; Adriane de Assis Lawisch Rodriguez; Tiago Bender Wermuth; Sarah Eller; Tiago Franco de Oliveira; Fabiano Raupp Pereira; Alexandre da Cas Viegas; Oscar Rubem Klegues Montedo; Maria Alice Prado Cechinel; Sabrina Arcaro (Environmental Science and Pollution Research, 2024)

Correction: Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Differential effects of fresh and composted organic wastes on soil bacterial community and maize growth - Guilherme Lucio Martins; Thierry Alexandre Pellegrinetti; Anderson Santos de Freitas; Gabriel Silvestre Rocha; Gabriel Gustavo Tavares Nunes Monteiro; Lucas William Mendes; Siu Mui Tsai; Fernando Carvalho Oliveira; Jussara Borges Regitano (Applied Soil Ecology, 2024)

Clinical and pathological findings of Africanized bee (Apis mellifera) envenomation in horses - Beatriz da Costa Kamura; Lukas Garrido Albertino; Ricardo Romera Cavallari; Larissa Queiroz de Souza; Lucas Troncarelli Rodrigues; Isabella Barros de Sousa Pereira; Noeme Sousa Rocha; Regina Kiomi Takahira; Wanderson Adriano Briscola Pereira; Alexandre Secorun Borges; José Paes de Oliveira-Filho; Rogério Martins Amorim (Toxicon, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Total replacing soybean meal with extruded urea in supplements on the intake, ruminal, and metabolic parameters of beef cattle during the rainy and wet-dry transition seasons - Gabriella Jorgetti de Moraes; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Gelson dos Santos Difante; Vanessa Zirondi Longhini; Rodrigo da Costa Gomes; Antonio Leandro Chaves Gurgel; Marcus Vinicius Garcia Niwa; Noemila Débora Kozerski; Marlova Cristina Mioto da Costa; Adriélli Dias Borges; et al. (Tropical Animal Health and Production, 2024)

An oblique transpressive soft-collision records the amalgamation of the Siderian-Orosirian Mineiro belt (Brazil) and the São Francisco paleo-craton (Kenorland Supercontinent): Insights from the Bom Sucesso metasedimentary sequence - Alvaro Balmant Pessamilio; Everton Marques Bongiolo; Ciro Alexandre Ávila; Gustavo Luiz Campos Pires; Bianca Saraiva Borges; Elson Paiva Oliveira; Reiner Neumann (Journal of South American Earth Sciences, 2024)

How much biochar is safe? Exploring potential ecotoxicological consequences for soil invertebrates and plants - Vanessa Borges da Costa; Allan Pretti Ogura; David Silva Alexandre; Matheus Bortolanza Soares; Luís Reynaldo Ferracciú Alleoni; Evaldo Luiz Gaeta Espíndola; Thandy Junio da Silva Pinto (Applied Soil Ecology, 2024)

Proteome and metabolome of Caryocar brasiliense camb. fruit and their interaction during development - Carlos Alexandre Rocha da Costa; Sidney Vasconcelos do Nascimento; Rafael Borges da Silva Valadares; Luíz Guilherme Malaquias da Silva; Gilson Gustavo Lucinda Machado; Isa Rebecca Chagas da Costa; Sayure Mariana Raad Nahon; Luiz José Rodrigues; Eduardo Valério de Barros Vilas Boas (Food Research International, 2024)

Making Global Climate Action work for nature and people: Priorities for Race to Zero and Race to Resilience - Idil Boran; Nathalie Pettorelli; Alexandre C. Köberle; Ricardo Aguiar Borges; Adriana De Palma; Deborah Delgado; Andrew Deneault; Alexandra Deprez; Pablo Imbach; Neil R. Jennings; Anke Manuela Salzmann; Oscar Widerberg; et al. (Environmental Science & Policy, 2024)

Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Development of a conceptual direct solvent extraction (DSX) route and a flowsheet to produce purified concentrated cobalt and nickel solutions representing sulfuric acid leach liquor of laterite - Alexandre Silva Guimarães; Georgio Patrício de Souza Resende; Iranildes Daniel dos Santos; Marcelo Borges Mansur (Hydrometallurgy, 2024)

Evaluation of different supportive treatments during packed cell volume replacement in calves naturally infected with tick fever agents - Alexandre Braga Scarpa; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Daniel de Castro Rodrigues; Nicolas Jalowitzki de Lima; Vando Edésio Soares; Lorena Lopes Ferreira; et al. (Veterinary Research Communications, 2024)

Effects of Myrcia pubipetala Miq (Myrtaceae) extract on innate inflammatory response - Pâmela Pacassa Borges; Larissa Benvenutti; Aline Lana Schneider; Marcelo Rodrigo Franke Echterhoff; Bruna Gonçalves Lopes; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Luciano Vitali; Michele Debiasi Alberton; Nara Lins Meira Quintão; José Roberto Santin; Isabel Daufenback Machado (Natural Product Research, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Methicillin-resistant Staphylococcus spp. investigation in hospitalized horses and contacting personnel in a teaching veterinary hospital - Giovane Olivo; Luiza Stachewski Zakia; Márcio Garcia Ribeiro; Maria de Lourdes Ribeiro de Souza da Cunha; Danilo Flávio Morais Riboli; Priscila Luiza Mello; Nathalia Bibiana Teixeira; César Erineudo Tavares de Araújo; José Paes Oliveira-Filho; Alexandre Secorun Borges (Journal of Equine Veterinary Science, 2024)

Isolation and primary culture of human abdominal aorta smooth muscle cells from brain-dead donors: an experimental model for vascular diseases - Carlos Alexandre Curylofo Corsi; Claudia Tarcila Gomes Sares; Fabiola Mestriner; Jéssyca Michelon-Barbosa; Vinicius Flora Dugaich; Timna Varela Martins; Alex Martins Násare; Roberta Ribeiro Costa Rosales; Maria Cecília Jordani; José Carlos Alves-Filho; Rodolfo Borges dos Reis; Mauricio Serra Ribeiro; et al. (Cell and Tissue Banking, 2024)

Pleural Empyema in Six Horses: A Retrospective Case Series - Lorena Battistin; Fabrício Moreira Cerri; Marcos Jun Watanabe; Regina Kiomi Takahira; Márcio Garcia Ribeiro; Noeme Sousa Rocha; José Paes de Oliveira-Filho; Alexandre Secorun Borges; Rogério Martins Amorim (Journal of Equine Veterinary Science, 2023)

Advances in genomic characterization of Urochloa humidicola: exploring polyploid inheritance and apomixis - Aline da Costa Lima Moraes; Marcelo Mollinari; Rebecca Caroline Ulbricht Ferreira; Alexandre Aono; Letícia Aparecida de Castro Lara; Marco Pessoa-Filho; Sanzio Carvalho Lima Barrios; Antonio Augusto Franco Garcia; Cacilda Borges do Valle; Anete Pereira de Souza; Bianca Baccili Zanotto Vigna (Theoretical and Applied Genetics, 2023)

Campomanesia guazumifolia infusion decreases human platelet aggregation by reducing cyclooxygenase 1 activity and its underlying mechanisms - Caroline Honaiser Lescano; Fernando Freitas de Lima; Taline Baganha Stefanello Catelan; Victor Hugo Dantas Guimarães; Ulisses Alves Pereira; Charles Martins Aguilar; Cláudia Andrea Lima Cardoso; Sérgio Henrique Sousa Santos; Alexandre Borges; Ivan Pires de Oliveira (Food Bioscience, 2023)

Repurposing miconazole and tamoxifen for the treatment of Mycobacterium abscessus complex infections through in silico chemogenomics approach - Laura Raniere Borges dos Anjos; Vinícius Alexandre Fiaia Costa; Bruno Junior Neves; Ana Paula Junqueira-Kipnis; André Kipnis (World Journal of Microbiology and Biotechnology, 2023)

Molecular interaction analysis of the lignans from Piper cubeba in complex with Haemonchus contortus phosphomethyltransferase - Alexandre Borges; Ivan Pires de Oliveira; Caroline Honaiser Lescano; Renato Luis Tame Parreira; Renato Pereira Orenha; Rosangela da Silva de Laurentiz (Veterinary Parasitology, 2023)

Detection of Equus caballus Papillomavirus in Equine Aural Plaque Samples - Cristiana R. Bromberger; Julia Rodrigues Costa; Mariana Herman; Juliana Mira Hernandez; Lukas Garrido Albertino; Carlos Eduardo Fonseca Alves; Alexandre S. Borges; Jose P. Oliveira-Filho (Journal of Equine Veterinary Science, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Design, synthesis, and in vitro antiplatelet aggregation activities of taiwanin C - Érika C. A. S. K. Daron; Wellington T. Negri; Alexandre Borges; Caroline H. Lescano; Edson Antunes; Rosangela S. de Laurentiz (Natural Product Research, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Potential in vitro action of an adenosine analog and synergism with penicillin against Corynebacterium pseudotuberculosis - Pedro Negri Bernardino; Carolina Lechinski de Paula; Ana Flávia Marques Pereira; Márcio Garcia Ribeiro; Vasco Ariston de Carvalho Azevedo; Alexandre Secorun Borges; Ary Fernandes-Júnior; José Paes Oliveira-Filho (Brazilian Journal of Microbiology, 2023)

Effect of space allowance during transport of Dorper x Santa Inês lambs on biochemical stress parameters and meat quality - Fredson Vieira e Silva; Iran Borges; Simone Koprowski Garcia; Hemilly Cristina Menezes de Sá; Vandenberg Lira Silva; Alexandre Ribeiro Araújo; Jeânio Alexandre de Lima; Laura Lúcia dos Santos Oliveira; Aylle Medeiros Matos; Fabio Luiz Buranelo Toral (Small Ruminant Research, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

Geochemistry of trace metals in surface sediments from the continental slope of the states of Sergipe and Alagoas, Northeastern Brazil - Carlos Alexandre Borges Garcia; Adnívia Santos Costa Monteiro; Silvânio Silvério Lopes da Costa; Maria de Lara Palmeira de Macedo Arguelho; Rennan Geovanny Oliveira Araújo; Maria Eulália Rocha Carneiro; José do Patrocínio Hora Alves (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Productive characteristics, chemical composition, in vitro digestibility, and degradation kinetics of two Brachiaria grasses at different regrowth ages - Juliana Caroline Santos Santana; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Marcus Vinicius Garcia Niwa; Gabriella Jorgetti de Moraes; Ângelo Herbert Moreira Arcanjo; Antonio Leandro Chaves Gurgel; Adriélli Dias Borges; Giovanna Manfre Formigoni; Gelson dos Santos Difante (Tropical Animal Health and Production, 2022)

In vitro and in silico cytotoxicity of hinokinin-loaded PLGA microparticle systems against tumoral SiHa cells - Regiane G. de Lima; Flavia C. R. Lisoni; Thais B. Picão; Fransérgio F. dos Santos; Renato P. Orenha; Alexandre Borges; Eduardo F. Molina; Renato L. T. Parreira; Márcio L. A. e Silva; Mario F. C. Santos; Rosangela da S. de Laurentiz (Natural Product Research, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Hypotensive activity of Campomanesia xanthocarpa leaf extract: beyond angiotensin II type 1 receptor blockage - Ingrid Beatriz de Melo Morais; Denise Brentan Silva; Carlos Alexandre Carollo; Marcos Luiz Ferreira-Neto; Patrícia Fidelis-de-Oliveira; Luiz Borges Bispo-da-Silva (Natural Product Research, 2021)

Effects of supplementation on production and age anticipation at first mating of ewe lambs in tropical pastures - Thais Fernanda Farias de Souza Arco; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Maria Inês Lenz Souza; Alexandre Menezes Dias; Gelson dos Santos Difante; Eliane Vianna da Costa e Silva; Fernando de Almeida Borges; Dyego Gonçalves Lino Borges; Kedma Leonora da Silva Monteiro Ferelli; Bruna Junqueira Rodrigues; Aline Aparecida da Silva Miguel; et al. (Tropical Animal Health and Production, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Analysis of the Influence of Water Quality Parameters in the Final WQI Result Through Statistical Correlation Methods: Mirim Lagoon, RS, Brazil, Case Study - Marlon Heitor Kunst Valentini; Gabriel Borges dos Santos; Victória Huch Duarte; Henrique Sanchez Franz; Hugo Alexandre Soares Guedes; Rubia Flores Romani; Bruno Muller Vieira (Water, Air, & Soil Pollution, 2021)

Chemical composition and potentiating action of Norfloxacin mediated by the essential oil of Piper caldense C.D.C. against Staphylococcus aureus strains overexpressing efflux pump genes - Antonio Linkoln Alves Borges Leal; Camila Fonseca Bezerra; Camila Confortin; Luiz Everson da Silva; Emanuelle Machado Marinho; Márcia Machado Marinho; Mayron Alves Vasconcelos; Terezinha Gonçalves da Silva; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Henrique Douglas Melo Coutinho; Humberto Medeiros Barreto; et al. (Archives of Microbiology, 2021)

Field Responses of Rice Stalk Stink Bug, Tibraca limbativentris, to Synthetic Sex Pheromone and Isomers of 1,10-Bisaboladien-3-ol - Thais F S De Freitas; E R Hickel; Ashot Khrimian; Miguel Borges; Mirian F F Michereff; José Alexandre Barrigossi; Raúl Alberto Laumann; S D Guggilapu; Josué Sant’Ana; Maria Carolina Blassioli-Moraes (Neotropical Entomology, 2021)

Calcium particle films promote a photoprotection on sweet potato crops and increase its productivity - Alexandre Passos Oliveira; Lia-Tânia Rosa Dinis; Nadja Tamires Borges Barbosa; Eloy Costa de Mattos; Pryanka Thuyra Nascimento Fontes; Marcelo Augusto Gutierrez Carnelossi; Jailson Lara Fagundes; Elizamar Ciríaco da Silva; Luiz Fernando Ganassali de Oliveira Junior (Theoretical and Experimental Plant Physiology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Heavy metal concentrations in Brazilian port areas and their relationships with microorganisms: can pollution in these areas change the microbial community? - Bruna Del Busso Zampieri; Vanessa da Costa Andrade; Roberta Merguizo Chinellato; Carlos Alexandre Borges Garcia; Marcos Antônio de Oliveira; Gunther Brucha; Ana Julia Fernandes Cardoso de Oliveira (Environmental Monitoring and Assessment, 2020)

Long-Term Spatial–Temporal Characterization of Cloud-to-Ground Lightning in the Metropolitan Region of Rio de Janeiro - Tales Bernardes Paulucci; Gutemberg Borges França; Renata Libonati; Alexandre M. Ramos (Pure and Applied Geophysics, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Interaction with Pantoea agglomerans Modulates Growth and Melanization of Sporothrix brasiliensis and Sporothrix schenckii - Rodrigo Almeida-Paes; Fábio Brito-Santos; Manoel Marques Evangelista Oliveira; Alexandre Melo Bailão; Clayton Luiz Borges; Glauber Ribeiro de Souza Araújo; Susana Frases; Célia Maria de Almeida Soares; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2019)

Influence of storage time and nutrient medium on recovery of fibroblast-like cells from refrigerated collared peccary (Pecari tajacu Linnaeus, 1758) skin - Luiza Bento de Queiroz Neta; Gabriela Pereira de Oliveira Lira; Alana Azevedo Borges; Maria Valéria de Oliveira Santos; Maria Bárbara Silva; Lhara Ricarliany Medeiros de Oliveira; Alexandre Rodrigues Silva; Moacir Franco de Oliveira; Alexsandra Fernandes Pereira (In Vitro Cellular & Developmental Biology - Animal, 2018)

Adsorbents made from textile scraps: preparation, characterization and application for removal of reactive dye - Jeferson Correia; Andressa Regina Vasques Mendonça; Selene Maria de Arruda Guelli Ulson de Souza; José Alexandre Borges Valle (Clean Technologies and Environmental Policy, 2018)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Characterization of dissolved organic matter in an urbanized estuary located in Northeastern Brazil - Maria de Lara Palmeira de Macedo Arguelho; José do Patrocínio Hora Alves; Adnívia Santos Costa Monteiro; Carlos Alexandre Borges Garcia (Environmental Monitoring and Assessment, 2017)

Redescription of Notarius grandicassis and Notarius parmocassis (Siluriformes; Ariidae), with insights into morphological plasticity and evidence of incipient speciation - Alexandre P. Marceniuk; Raquel Siccha-Ramirez; Ronaldo Borges Barthem; Wolmar Benjamin Wosiacki (Systematics and Biodiversity, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

NMDA Receptors and Oxidative Stress Induced by the Major Metabolites Accumulating in HMG Lyase Deficiency Mediate Hypophosphorylation of Cytoskeletal Proteins in Brain From Adolescent Rats: Potential Mechanisms Contributing to the Neuropathology of This Disease - Carolina Gonçalves Fernandes; Paula Pierozan; Gilberto Machado Soares; Fernanda Ferreira; Ângela Zanatta; Alexandre Umpierrez Amaral; Clarissa Günther Borges; Moacir Wajner; Regina Pessoa-Pureur (Neurotoxicity Research, 2015)

A single set of exhaustive exercise before resistance training improves muscular performance in young men - Andreo Fernando Aguiar; Cosme Franklim Buzzachera; Rafael Mendes Pereira; Vanda Cristina Sanches; Renata Borges Januário; Rubens Alexandre da Silva; Lucas Maciel Rabelo; André Wilson de Oliveira Gil (European Journal of Applied Physiology, 2015)

Genetic progress during 22 years of black bean improvement - Luis Cláudio de Faria; Patrícia Guimarães Santos Melo; Helton Santos Pereira; Adriane Wendland; Simone Ferreira Borges; Israel Alexandre Pereira Filho; José Luiz Cabrera Diaz; Marcelo Calgaro; Leonardo Cunha Melo (Euphytica, 2014)

Physical and chemical characteristics of water from the hydrographic basin of the Poxim River, Sergipe State, Brazil - Antenor Oliveira de Aguiar Netto; Carlos Alexandre Borges Garcia; José do Patrocínio Hora Alves; Robério Anastácio Ferreira; Marinoé Gonzaga da Silva (Environmental Monitoring and Assessment, 2013)

Planning for optimal conservation of geographical genetic variability within species - José Alexandre Felizola Diniz-Filho; Dayane Borges Melo; Guilherme de Oliveira; Rosane Garcia Collevatti; Thannya Nascimento Soares; João Carlos Nabout; Jacqueline de Souza Lima; Ricardo Dobrovolski; Lázaro José Chaves; Ronaldo Veloso Naves; Rafael Dias Loyola; Mariana Pires de Campos Telles (Conservation Genetics, 2012)

Assessment of trace metals pollution in estuarine sediments using SEM-AVS and ERM–ERL predictions - Carlos Alexandre Borges Garcia; Elisangela de Andrade Passos; José do Patrocínio Hora Alves (Environmental Monitoring and Assessment, 2011)

A geographical genetics framework for inferring homing reproductive behavior in fishes - Mariana Pires de Campos Telles; Rosane Garcia Collevatti; Marcio Candido da Costa; Ronaldo Borges Barthem; Nelson Jorge da Silva; Advaldo Carlos Souza Neto; José Alexandre Felizola Diniz-Filho (Genetica, 2011)

Genes Potentially Relevant in the Parasitic Phase of the Fungal Pathogen Paracoccidioides brasiliensis - Clayton Luiz Borges; Alexandre Melo Bailão; Sonia N. Báo; Maristela Pereira; Juliana Alves Parente; Célia Maria de Almeida Soares (Mycopathologia, 2011)

Assessment of trace metal concentration in feathers of seabird (Larus dominicanus) sampled in the Florianópolis, SC, Brazilian coast - Edison Barbieri; Elisangela de Andrade Passos; Alexandre Filippini; Izaias Souza dos Santos; Carlos Alexandre Borges Garcia (Environmental Monitoring and Assessment, 2010)

Comparison of transcription of multiple genes during mycelia transition to yeast cells of Paracoccidioides brasiliensis reveals insights to fungal differentiation and pathogenesis - Juliana Alves Parente; Clayton Luiz Borges; Alexandre Melo Bailão; Maria Sueli S. Felipe; Maristela Pereira; Célia Maria de Almeida Soares (Mycopathologia, 2008)

Synthesis and antiviral activity of new 4-(phenylamino)/4-[(methylpyridin-2-yl)amino]-1-phenyl-1H-pyrazolo[3,4-b]pyridine-4-carboxylic acids derivatives - Alice Maria Rolim Bernardino; Alexandre Reis de Azevedo; Luiz Carlos da Silva Pinheiro; Júlio Cesar Borges; Vinícius Lucio Carvalho; Milene Dias Miranda; Marcelo Damião Ferreira de Meneses; Marcelo Nascimento; Davis Ferreira; Moacyr Alcoforado Rebello; Viveca Antonia Giongo Galvão da Silva; Izabel Christina Palmer Paixão de Frugulhetti (Medicinal Chemistry Research, 2007)

Sex Attractant Pheromone from the Rice Stalk Stink Bug, Tibraca limbativentris Stal - Miguel Borges; Michael Birkett; Jeffrey R. Aldrich; James E. Oliver; Mitsuo Chiba; Yasuhiro Murata; Raul A. Laumann; José Alexandre Barrigossi; John A. Pickett; Maria C. B. Moraes (Journal of Chemical Ecology, 2006)